Análise de critérios de entrada em um novo mercado para empresas exportadoras da Serra Gaúcha - Ost, Nicole (My University, 2018)
Internationalization offers many benefits for companies, however, to analyze the criteria before exporting to the destination market is very important in order to reduce the risks that this process contemplates. The present study had as objective to analyze which are the most important criteria for selection of the target markets for exporting companies of Serra Gaúcha. To achieve this goal, a survey was carried out with 49 exporting companies. The survey was composed of 70 previously selected criteria, where the respondent assessed the importance of the criteria and how frequent the criteria are analyzed when exporting to a new market. The results were analyzed through the mean obtained in relation to the importance and the frequency of analysis of the criteria. The results showed that the most important criteria and analyzed more frequently by the exporting companies are commercial criteria.(sic)
A internacionalização proporciona diversos benefícios para as empresas. No entanto, a análise de critérios do mercado de destino prévia à exportação é de suma importância para diminuir os riscos que este processo contempla. O presente estudo teve como objetivo analisar quais são os critérios mais importantes para seleção dos mercados alvo para empresas exportadoras da Serra Gaúcha. Para alcançar este objetivo foi realizada uma pesquisa com 49 empresas exportadoras, a pesquisa foi composta por 70 critérios, previamente selecionados, onde o respondente avaliou a importância dos critérios e a frequência que estes são analisados ao exportar para um novo mercado. Os resultados foram analisados através da média obtida em relação à importância e à frequência de análise dos critérios. Os resultados apontaram que os critérios mais importantes e analisados com maior frequência pelas empresas exportadoras são critérios comerciais.(sic)
Keywords: Empresas comerciais exportadoras - Serra, Região (RS); Exportação; Mercadorias - Exportação